Undergraduate neurology in the 21st Century and the bedside tradition. Issue 2 (6th November 2013) - Manford, Mark
Abstract : Neurology teaching highlights clinical skill and is appealing to students but after they qualify the subject has a notorious reputation. Changes in clinical practice with fewer inpatients provide challenges to traditional teaching, but there are nevertheless opportunities for combining creative teaching methods with modern technology to provide a rich, enduring and relevant learning experience that can create a generation of clinicians not intimidated by a tendon hammer.